Kia Whai Reo Te Wao - Hoskins, Hemi (Te Kaharoa, 2012)
The traditional domains in which the Maori language has been able to flourish or even survive have been severely reduced as a result of colonisation and associated language loss. The breakdown of traditional Maori communities and the economic and social pressures experienced by Maori have all contributed to our language decline as our people increasingly left their traditional communities for the urban centres in the hope of securing a better existence for them and their whanau.  This move away from papakainga combined with the restrictions upon access to traditional mahinga kai (food gathering places) has meant the domain of te taiao (the environment) and associated language around the hunting and gathering practices of our tupuna (ancestors )are now held by a declining number of repositories of the reo. Furthermore advances in technology, techniques and equipment used in the modern harvest of wild foods have occurred faster than the evolution of the language.The survival of the language and transmission of its knowledge now requires collaboration between those with knowledge of the language and those engaged in the environment. This will enable the development of vocabulary to keep up with the changes while maintaining the traditional knowledge base and perspective. This paper aims to examine methods of collaborating those with the specific knowledge of each field in an effort to regenerate the usage of the language in the domain from which it finds reference.